Ventilación mecánica en el síndrome de dificultad respiratoria aguda en neonato pretermino de sexo masculino. - Guerrero Terán, Sergio David (2020)
The acute respiratory distress syndrome (SDRA), initially described by Ashbaugh in 1967, consists of an acute picture of hypoxemic respiratory failure (PaO2 / FiO2 ≤ 200) with the presence of bilateral infiltrates in the simple chest plate related to diffuse pulmonary edema non cardiogenic. Most patients with acute respiratory distress syndrome require mechanical ventilation during their evolution, conventional ventilation optimized according to lung protection criteria being the current quality standard. Other mechanical ventilation strategies such as HFOV, also based on the concepts of alveolar recruitment and maintenance of adequate lung volume, may be useful alternatives.